The Linguistic Factors That Affect Poor Reading Comprehension Among Libyan Students - alowalid, abdulhakim faraj; Mujiyanto, Januarius; Anggani Linggar Bharati, Dwi (English Education Journal, 2018)
Reading may be one of the most important skills a person may have. The National Reading Panel has stated that there are five specific practices teachers should use when teaching children to read or while helping them improve their reading skills. Reading comprehension requires readers to really know and understand what they read. This research used quantitative research. Instrument for collecting data in this study is test instruments. It will use test items with numerical data. The data used on improving students' reading comprehension were obtained by observing to Libyan’s students in Semarang. The worksheet was spread to Libyan students and they did the worksheet. The data about reading comprehension and worksheet will be in the form of numerical data. Data analysis in this study used descriptive analysis techniques, which serves to provide an overview of the data of the study variables. Based on these results, the answer that often appears on all items of reading comprehension can be interpreted that respondents usually try to understand the text being read. Factor that affects reading comprehension ability is spelling. The three linguistic factors studied, the most influential factor on reading comprehension is spelling.